Analysis of Incompatible Crossmatch Results Based on Autoimmune Haemolytic Anemia Characteristics (Aiha) at Pmi Semarang City in 2021-2022 - syarifah, Syarifah; Prasetyaswati, Betty; Pangestuti, Dewi (MultiTech Publisher, 2023)
Background: Crossmatch with positive Major, positive Minor, positive Auto Control results, a DCT examination is carried out whose positive results are suspected to indicate an AIHA diagnosis in the patient, if given there must be a letter from the doctor treating the patient requesting blood to be transfused. Method : Observational descriptive design with a cross-sectional approach, the results of incompatible crossmatch of autoimmune haemolytic anemia patients in 97 patients with elderly characteristics at PMI Semarang City in January 2021-December 2022. Data collection methods using secondary data were analyzed using univariate and bivariate with Microsoft Excel 2010 and SPSS Version 26 Results: Most crossmatch incompatibilities were found at age > 56 years (66%), Major Positive (99%), Positive AutoControl (99%), Diagnosis of Autoimmune Haemolytic Anemia (AIHA). The results of the bivariate test showed that the major crossmatch was -0.073 while the Auto Control was 0.142. This indicates that age does not affect the results of incompatible crossmatches. Conclusion: Most of the needs were met by female sex as many as 118 patients with positive rhesus blood type and dominated by the age of 1-10 years. Analysis of incompatible crossmatch results based on the characteristics of patients with autoimmune haemolytic anemia at PMI Semarang City in 2021-2022 with the result that age can affect the results of incompatible crossmatches.